Effects of small molecules on coal liquefaction. Issue 14 (18th July 2017) - Wang, Ying-Chun; Xue, Yong-Bing; Wang, Xiao-Xiao; Cui, Su-Hua; Zhang, Zhi-Feng
ABSTRACT: Liquefaction experiments on raw coal, extracted coal, and backfill coal of small molecules were carried out, respectively, to study the effects of small molecules on coal liquefaction. The results indicated that small molecules could provide active hydrogen in the liquefaction process, but compared with the strong hydrogen-donating solvent tetralin, their role was very limited. Moreover, it's found that after the extraction of hydrogen-rich small molecules in coal, the total conversion rate rose rather than fell, because the surface pore structure of coal was loosened by extraction, which smoothened the pathway for strong hydrogen-donating solvent to provide hydrogen, thereby improving hydrogen supply efficiency.